Development of education in Ukraine in the XVIII - XIX centuries - Боченко, О. В. (Scientific notes of the pedagogical department, 2019)
The purpose of the article: to study the state of education in Ukraine in the XVIII – XIX centuries: the opening of new schools, gymnasiums, classes, colleges; children of what social groups of the population received education; what subjects were taught; conditions for the implementation of the educational process in these institutions and their role in the cultural development of Ukraine; analyze the changes that took place in education at that time; pay special attention to the role of the Collegium on the development of the city of Kharkov.In the XVIII – XIX centuries various schools began to open. They worked at monasteries and churches. The first school was opened in 1675 in Akhtyrka. In 1732, there were already 131 parochial schools in Ukraine. Children received basic knowledge and the ability to read, count, write. The teachers were the ministers of the church. After a while, bishop schools began to open.In 1726, such a school was transferred from Belgorod to Kharkov. This school later became known as the Kharkov Collegium. The first stage of the formation of the collegium lasted from 1726 to the mid-30s of the XVІІth century. At this time there was a paperwork and construction of the building. Supervised the colleague of Epiphanius Tikhorsky. In 1729, this school for children of the clergy was united with the Pokrov Church. In 1725 there were 300 pupils in this school, in 1727 there were 422 pupils, in 1737 there were 522 pupils, in 1823 there were 240 pupils, in 1833 there were 256 pupils. The collegium studied children of the clergy and other segments of the population. In 1840 17% of such children studied at the school, in 1759 – 11%, in 1762 – 12%, in 1781 – 11%, in 1790 – 17%, in 1812 – 12%, in 1816 – 9%, in 1821 – 0%, in 1831 – 0%. Students, who paid for their education and students, who studied for public money studied at the collegium. In 1773 there were 24 such students, in 1774 – 30, in 1720 – 60 students. For orphans collegium had a hostel. Pupils could make money themselves during the exercise. They worked as teachers, tutors.In 1792 there were 455 students and 13 teachers in the school; in 1813 – 769 students 11 teachers. The collegium taught: philosophy, history, geography, drawing, theology, French, German, Latin. In 1768, when the collegium appeared, «additional» classes for children of nobles. These classes prepared teachers, translators, surveyors, land surveyors, cartographers, musicians, singers. Training was free. Pupils could attend the college and «extra» classes. In 1773 there were 125 pupils in these classes (state school), in 1785 – 237 pupils, in 1795 – 260 pupils. In 1798 the main, small and state school merged into the main national school. In 1789 a gymnasium №1 was opened in Kharkov, in 1841 – the second; in 1870 – the Mariinsky gymnasium; in 1873 – a real school; in 1812 – the Institute of Noble Maidens. Since 1817 the Kharkov Collegium began to work according to the regulations of the religious schools.Conclusions: ХУІІІ, ХІХ centuries became the time of active opening of various educational institutions: schools, colleges, classes, gymnasiums, which influenced the development of Kharkov as a cultural center.